Muhammadiyah's Contribution inthe Renewal of Islamic Religious Education in Indonesia - Maimori, Romi; Iswantir, Iswantir; Eliwatis, Eliwatis; Herawati, Susi; Irwandi, Irwandi; Efendi, Indra (Yayasan Minang Darussalam, 2022)
This study aims to determine the contribution of Muhammadiyah to the world of education in Indonesia both before and after the Independence of the Republic of Indonesia in 1945. The method used in this research is the method used in this research is the library research method, with data collection techniques. data by identifying discourse from books, papers or articles, magazines, journals, or other information related to the title of writing this article, namely Muhammadiyah and Islamic Religious Education in Indonesia, from this research it is divided into two categories, namely the concept of Muhammadiyah and Muhammadiyah education and The Development of Islamic Religious Education in Indonesia From the results of this study it was found that the Muhammadiyah association was one of the organizations that was born before independence and was able to lay the initial foundation for the revival of education in Indonesia from a pattern of education. from traditional to modern educational patterns. This pattern has actually produced intellectual cadres who are of good quality in general science as well as religious knowledge and values